CHARACTERIZATION OF ASHES FROM FOREST BIOMASS COMBUSTION IN BOILERS: A SYSTEMIC VIEW OF POTENTIAL APPLICATIONS - Henne, Reny Aldo; Brand, Martha Andreia; Schein, Viviane Aparecida Spinelli; Pereira, Ederson Rodrigues; Schveitzer, Bianca (Floresta, 2019)
The description of the ash formation process during biomass burning and the determination of its physical and energetic properties are fundamental for the improvement of energy generation processes and the prospection of this residue’s reuse. Thus, this study aimed to evaluate the energy quality of the biomass burned and the ash generated in the boiler of a thermal power plant that uses forest biomass as fuel, as well as to consider the potential applications of this residue. To this end, the following properties of the ashes collected at four different collection points of the boiler (readler, hopper, scrubber, and decanter) were determined: moisture content; organic and inorganic elemental composition; proximate composition; and gross calorific value. The biomass was calcined in the laboratory and evaluated together with the ashes from calcination to compare the results. Although the wood biomass used by the thermal power plant was a residual material, it presented high energy quality. The physical, chemical and energetic properties of the ashes produced in the boiler varied according to the thermal power plant’s operation conditions. The ashes collected in the hopper showed a high energy potential, but further studies about furnace reconfiguration and retention time in the chamber are needed to allow its efficient burning for energy generation. Ashes from the hopper have the potential to be used as household charcoal and as biochar. The results obtained in this study are fundamentally important and provide a basis for further studies.